IV3000 semi-occlusive dressing use in simple and complex fingertip injuries: efficacy and affordability. (2nd April 2022) - Cheang, Catherine Jenn Yi; Khan, Muhammad Adil Abbas; Jordan, Daniel J; Nassar, Kazem; Bhatti, Dujanah Siddique; Rafiq, Sadia; Hogg, Fiona J; Waterston, Stuart W
Abstract : Objective: This study aimed to explore the efficacy of the IV3000 semi-occlusive, transparent adhesive film dressing in the non-surgical management of simple as well as more complex fingertip injuries. Method: In this qualitative study, patients with fingertip injuries were prospectively recruited and treated conservatively with the dressing between 2015 and 2017. Inclusion criteria included any fingertip injury with tissue loss and patient consent for non-surgical treatment consistent with the study protocol. Exclusion criteria included injuries needing surgical intervention for tendon injury or exposure, joint dislocations, distal phalangeal fractures requiring fixation, bone exposure, isolated nail bed lacerations and any patients eligible for surgical repair who did not wish to be managed conservatively. Results: A total of 64 patients took part in the study. The patients treated with the dressing were asked to rate functional outcome, of whom 40 (62.5%) patients reported the outcome as 'excellent', 19 (29.7%) as 'satisfactory', five (7.8%) as 'indifferent' and none (0%) as 'unsatisfactory'. A reduced pulp volume at completion of healing was felt by 21 (32.8%) patients, but all patients were 'satisfied' with the aesthetic appearance of their fingertips at final clinical review. Average healing time was 4.5 weeks across the group, with the average time for return to work being just under one week. We estimate a 60% reduction in cost with the conservative versus the surgical management option. Conclusion: This study showed that, for participants, the IV3000 dressing was an affordable and effective option for the conservative treatment of simple fingertip injuries and in the management of more complex fingertip injuries.